Who cares? : The economies of dignity - WARING,MARILYN; Waring, Marilyn (London : Commonwealth Secretariat, 2011)
"At the centre of the HIV/AIDS response are the 12 million people who need care and treatment. Those who are ill require support from carers who provide physical, social and psychological support. Yet these carers - essential actors in the response - are often invisible to the system that relies on them. The writers argue that focusing on the carer, at the household level, directs assistance where it is most effective and most needed, will respect human rights, and will help achieve the millennium development goals in health."--Publisher.
1. Introduction -- 2. Dignity in Daily Life: A Conceptual Framework -- 3. The Conditions of Choice: Capability Servitude in Unpaid HIV Care -- 4. Stigma and Discrimination: The Situation of People Living with HIV and Their Carers -- 5. The Duty of Care: The Right to Health in Hospital Settings -- 6. HIV and Gender-based Violence: The Rights of Unpaid Women and Girl Carers -- 7. A Case for Justice: The Rights of Prisoners with HIV -- 8. Dignity Overdue: National HIV Strategies and Unpaid Carers' Rights.
DVD in pocket.
Keywords: Caregivers; AIDS (Disease)